The Function of Metformin in Aging-Related Musculoskeletal Disorders - Song, Yanhong; Wu, Ziyi; Zhao, Ping (Frontiers in Pharmacology, 2022)
Metformin is a widely accepted first-line hypoglycemic agent in current clinical practice, and it has been applied to the clinic for more than 60 years. Recently, researchers have identified that metformin not only has an efficient capacity to lower glucose but also exerts anti-aging effects by regulating intracellular signaling molecules. With the accelerating aging process and mankind’s desire for a long and healthy life, studies on aging have witnessed an unprecedented boom. Osteoporosis, sarcopenia, degenerative osteoarthropathy, and frailty are age-related diseases of the musculoskeletal system. The decline in motor function is a problem that many elderly people have to face, and in serious cases, they may even fail to self-care, and their quality of life will be seriously reduced. Therefore, exploring potential treatments to effectively prevent or delay the progression of aging-related diseases is essential to promote healthy aging. In this review, we first briefly describe the origin of metformin and the aging of the movement system, and next review the evidence associated with its ability to extend lifespan. Furthermore, we discuss the mechanisms related to the modulation of aging in the musculoskeletal system by metformin, mainly its contribution to bone homeostasis, muscle aging, and joint degeneration. Finally, we analyze the protective benefits of metformin in aging-related diseases of the musculoskeletal system.